K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 8 2017

a)\(x^2-y^2-x-y=\left(x-y\right)\left(x+y\right)-\left(x+y\right)\)

                                  \(=\left(x+y\right)\left(x-y-1\right)\)

b)\(x^2-5x+5y-y^2=\left(x-y\right)\left(x+y\right)-5\left(x-y\right)\)

                                       \(=\left(x-y\right)\left(x+y-5\right)\)

21 tháng 8 2017

a) (x-y)(x+y)-(x+y)=(x+y)(x-y-1)     b) (x^2-y^2)-(5x-5y)=(x-y)(x+y)-5(x+y)=(x+y)(x-y-5)     c)  (x^3+1)-3x(x+1)=(x+1)(x^2-x+1)-3x(x+1)=(x+1)(x^2-4x+1)

16 tháng 11 2018

b.10x(x-y)-6y(y-x)=10x(x-y)+6y(x-y)=(10x+6y)(x-y)

16 tháng 11 2018

c.3x2+5y-3xy-5x=(3x2--3xy)-(5x-5y)=3x(x-y)-5(x-y)=(3x-5)(x-y)

16 tháng 12 2018

\(10x\left(x-y\right)-6y\left(y-x\right)\)

\(=10x\left(x-y\right)+6y\left(x-y\right)\)

\(=\left(10x+6y\right)\left(x-y\right)\)

9 tháng 10 2018

a) 5x3y - 30x2y + 45xy

= 5xy.(x2 - 6x + 9)

= 5xy.(x2 - 2.3.x + 32)

= 5xy.(x-3)2

b) x3 - 2x2 - x+2

= x2.(x-2) - (x-2)

= (x-2).(x2-1)

= (x-2).(x-1).(x+1)

c) 3x.(x-y) - (y-x)2

= 3x.(x-y) - (x-y)2

= (x-y).( 3x - x + y)

= (x-y).( 2x+y)

20 tháng 5 2018

a) x2 + 6x + 9 = x2 + 2 . x . 3 + 32 = (x + 3)2

b) 10x – 25 – x2 = -(-10x + 25 +x2) = -(25 – 10x + x2)

                         = -(52 – 2 . 5 . x – x2) = -(5 – x)2

c) 8x3 - 1/8 = (2x)3 – (1/2)3 = (2x - 1/2)[(2x)2 + 2x . 12 + (1/2)2]

                    = (2x - 1/2)(4x2 + x + 1/4) 

d)1/25x2 – 64y2 = (1/5x)2(1/5x)2- (8y)2 = (1/5x + 8y)(1/5x - 8y)

13 tháng 8 2020

a,\(\frac{1}{5}x^2y\left(15xy^2-5y+3xy\right)=3x^3y^3-x^2y^2+\frac{3}{5}x^3y^2\)

b,\(5x^3-5x=5x\left(x^2-1\right)=5x\left(x-1\right)\left(x+1\right)\)

c, \(3x^2+5y-3xy-5x=3x\left(x-y\right)-5\left(x-y\right)\)

\(=\left(3x-5\right)\left(x-y\right)\)

13 tháng 8 2020

1) 1/5x2y( 15xy2 - 5y + 3xy ) = 3x3y3 - x2y2 + 3/5x3y2

2) a) 5x3 - 5x = 5x( x2 - 1 ) = 5x( x2 - 12 ) = 5x( x - 1 )( x + 1 )

b) 3x2 + 5y - 3xy - 5x = ( 3x2 - 3xy ) + ( 5y - 5x )

                                  = 3x( x - y ) + 5( y - x )

                                  = 3x( x - y ) + 5[ -( x - y ) ]

                                  = 3x( x - y ) - 5( x - y )

                                  = ( 3x - 5 )( x - y )